Dampak Pembangunan Keuangan Terhadap Pembangunan Manusia di Negara Berkembang - Friesshya, Olia Vioni Cici; Marta, Joan (Media Riset Ekonomi Pembangunan (MedREP), 2025)
This study aims to analyze the impact of financial development on human development in developing countries. This study uses macro data sourced from the World Bank and the International Monetary Fund. This study analyzes 30 developing countries from 2005-2022. The research uses a quantitative research design using the data analysis method, namely Fully-Modified OLS (FMOLS) in E-views 12. The results of this analysis show that broad money is positive and significant on the human development index and tertiary school enrollment. Private sector credit has a positive and significant effect on human development index and tertiary school enrollment. This study shows the impact of financial development on human development in developing countries. This research is expected to serve as a basis for policy planning in order to improve human development in developing countries.